2013
DOI: 10.1111/mec.12498
|View full text |Cite
|
Sign up to set email alerts
|

Genetics at the verge of extinction: insights from the Iberian lynx

Abstract: Population viability might become compromised by the loss of genetic diversity and the accumulation of inbreeding resulting from population decline and fragmentation. The Iberian lynx (Lynx pardinus) provides a paradigmatic example of a species at the verge of extinction, and because of the well-documented and different demographic histories of the two remaining populations (Doñana and Andújar), it provides the opportunity to evaluate the performance of analytical methods commonly applied to recently declined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 72 publications
(138 reference statements)
7
68
1
Order By: Relevance
“…2012; Casas‐Marce et al. 2013). These species had H O prior to reintroduction or translocation programs that varied from 0.167 for the Florida panther, (Johnson et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2012; Casas‐Marce et al. 2013). These species had H O prior to reintroduction or translocation programs that varied from 0.167 for the Florida panther, (Johnson et al.…”
Section: Discussionmentioning
confidence: 99%
“…2012; Casas‐Marce et al. 2013). There are two remaining remnant populations of the Iberian lynx, which show evidence of inbreeding depression, including reduced genetic diversity (Palomares et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such separation is at least five times the maximum successful dispersal distance (Ferreras et al 2004) and, indeed, no individual born in one subpopulation has been reported to settle into the other by natural means. A marked genetic differentiation further supports demographic isolation between both subpopulations for at least ten generations (Casas-Marcé et al 2013). As >50% of total AOO is placed in a single isolated locality that might not support a viable population, the geographic range of the Iberian lynx can be considered as severely fragmented (IUCN Standards and Petitions Subcommittee 2014).…”
Section: Number Of Localities and Fragmentationmentioning
confidence: 98%
“…For example, the population with specific adaptive alleles can be identified and used to supplement the endangered population or reintroducing species into the habitat in which the natural population has vanished (Simpson et al 2017). The loss of genetic diversity and inbreeding accumulation due to fragmentation and decrease of population may compromise the viability of population (Casas-Marce et al 2013). An example of organism showing this is the Iberian lynx (Lynx pardinus) which is in the edge of extinction (Godoy, 2016).…”
Section: Fig 2: Summarized Factors That Have Negative Impacts On Biomentioning
confidence: 99%